ANALYSIS OF FAMILY PLANNING DROPOUTS IN WOMEN OF REPRODUCTIVE AGE - Putra Apriadi Siregar; Nurhayati Nurhayati; Desty Adinda; Muhammad Ancha Sitorus; Robani Catursaptanie; Evalina Franciska Hutasoit (Poltekkes Kemenkes Semarang, 2022)
The Family Planning Program (FPP) is one of the strategies carried out by the government to suppress the increase in population growth. Unfortunately, women of reproductive age (WRA) often stop participating in FPP or drop it out, unaware of increasing the risk of conception. This study uses secondary data from the 2017 IDHS for 945 WRAs who have used modern FPP methods. It uses cross-tabulation to determine the distribution of husbands' approval regarding the FPP method, wanting more children, side effects of family planning, the role of family planning service providers, and the incidence of dropping out of FPP in North Sumatra Province. The results indicated that 238 out of 707 WRAs (25.8%) dropped out of FPP. The FPP dropping out in North Sumatra Province mostly occurred to WRAs who experienced side effects of FPP methods (238 WRAs) and who changed their minds to want more children (67 WRAs). The BKKBN of North Sumatra Province must provide training to FPP service providers on the side effects of the methods to improve their counseling skills, which must be used properly to serve the WRAs before they decide to use contraceptives.